Analysis of sequence distribution in siloxane copolymers to study the mechanism of polymerization of cyclosiloxanes - Cypryk, M. (Polimery, 2022)
29Si NMR spectroscopy was used to establish the sequence distribution in polymers prepared by ring opening of 2,2,4,4-tetramethyl-6,6-diphenykyclotrisiloxane in the presence of anionie (lithium silanolate in tetrahydrofuran (THF), a (1:1) potassium silanolate-18-crown-6 ether mixture in toluene, and tetramethylammonium silanolate in toluene) and cationic (trifluoromethanesulfonic acid and trifluoromethanesulfonic acid-trimethylsilyl trifluoromethanesulfonate) initiators. The pentad sequence distribution in the chains was deduced from 29Si NMR spectra and was simulated by numerical and Monte Carlo methods based on the first order Markov chain statistics (Scheme A, equation set 2) in combination with the determination of sequences at chain ends. Ring-opening probabilities were evaluated at three nonequivalent positions a, b and c (Table 1), whereby the chemoselectivity of polymerization and the regioselectivity of monomer’s ring opening were determined. The polymerization proved to be highly chemoselective; the side reactions involving cleavage of siloxane bonds were found to be insignificant up to high monomer conversions (>95%). The first order Markov chain model showed the regioselectivity of monomer addition to the active center to be low, i.e., with each initiating system examined, the siloxane ring was opened at the three nonequivalent positions at significant levels of probability and in the proportions related to the type of the polymerization system (Table 1). This mechanism was discussed for both anionie and cationic polymerizations. The proportions of monomer openings exhibited the specific mechanistic features of the initiating systems used. Quantum-mechanical (ab initio) calculations showed the lack of regioselectivity in the polymerization systems to be attributable to phenyl ring-cation (counter-ion) interactions that stabilize the structures in which the cation interacts with the less basic oxygen atom linked to the Ph2Si group.